2018
DOI: 10.1038/s41598-018-29509-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ageing on 11C-Hydroxyephedrine Uptake in the Rat Heart

Abstract: We aimed to explore the impact of ageing on 11C-hydroxyephedrine (11C-HED) uptake in the healthy rat heart in a longitudinal setting. To investigate a potential cold mass effect, the influence of specific activity on cardiac 11C-HED uptake was evaluated: 11C-HED was synthesized by N-methylation of (−)-metaraminol as the free base (radiochemical purity >95%) and a wide range of specific activities (0.2–141.9 GBq/μmol) were prepared. 11C-HED (48.7 ± 9.7MBq, ranged 0.2–60.4 μg/kg cold mass) was injected in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Another factor affecting uptake and retention is the specific activity of the radiotracer, as has been demonstrated by our research on 11 C-HED in rat hearts. 38 . The cold mass effect should certainly be addressed after establishing a fully repeatable radiolabeling protocol suitable for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor affecting uptake and retention is the specific activity of the radiotracer, as has been demonstrated by our research on 11 C-HED in rat hearts. 38 . The cold mass effect should certainly be addressed after establishing a fully repeatable radiolabeling protocol suitable for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The density of sympathetic nerve terminals, as assessed by 123 I-MIBG scintigraphy and 11 C-HED PET, remains stable or declines with age. [40][41][42] In contrast, several 11 C-methylquinuclidinyl benzilate PET studies have shown that muscarinic cholinergic receptors are upregulated in patients with dilated cardiac myopathy and also in remote nondamaged territories in patients with myocardial infarction. [43][44][45] Thus, cholinergic cardiac receptor upregulation is clearly an adaptive response in several types of heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, different doses of m HED were applied with constant concentrations of metaraminol in a recently published study. A washout or decreased time activity curve was observed from an applied concentration of 10 µg/kg bodyweight m HED [16]. The IC 50 value of m HED towards NET drug inhibition was reported as 0.42 µM (competitive inhibition) by Foley at al.…”
Section: Discussionmentioning
confidence: 99%